Learner Autonomy Through Teacher Agency in Language Education: A Synthesis of Contemporary Research - Andri, Dafitri; Azis, Kholil (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This qualitative literature review synthesizes contemporary research (2020–2024) on the interplay between learner autonomy and teacher agency in language education. Findings reveal learner autonomy as a multifaceted construct encompassing cognitive (metacognitive awareness), affective (motivation), and behavioral (self-regulation) dimensions, essential for lifelong language learning. Crucially, teacher agency emerges as the cornerstone for fostering autonomy, with educators adopting dynamic roles—facilitator, guide, evaluator, instructional designer—to empower students. Structural barriers (e.g., rigid curricula, exam-oriented systems), cultural constraints, and institutional limitations impede implementation, yet teachers’ professional freedom, reflective practices, and context-sensitive pedagogies bridge theory-practice gaps. The study identifies systemic challenges, including learner dependence, time constraints, and inadequate teacher training. Implications call for educational policies prioritizing decentralized decision-making, tailored professional development, and flexible curricula. Future research should employ mixed-method designs to explore socio-cultural mediators of autonomy. Sustainable frameworks must position teacher agency and learner autonomy as interdependent pillars to cultivate self-directed learners in globalized contexts.